The influence of learning style, family climate, and self confidence on learning outcomes in mathematics of Senior High Schools in Somba Opu - Amriadi, Amriadi (Journal of Educational Science and Technology (EST), 2017)
This study is an expost facto research that aims to determine the influence of learning styles, family climate, and self-confidence in mathematics learning outcomes. The research population of students in grade XI IPA SMA Negeri Somba Opu District 2015/2016. Sampling technique with proportional stratified random sampling. Total sample of 158 students. Instruments used learning style tests, family climate questionnaires, confidence questionnaires, and mathematics learning outcomes. Data were obtained by using regression analysis. The results of the study reveal that (1) there is influence of learning style on learning outcomes in Mathematics subject, (2) there is influence of family climate on learning outcomes in Mathematics subject, (3) there is no influence of self confidence on learning outcomes in Mathematics subject, (4) there is interaction between learning style and family climate on learning outcomes in Mathematics subject, (5) there is interaction between learning style and self confidence on learning outcomes in Mathematics subject, (6) there is no interaction between family climate and self confidence on learning outcomes in Mathematics subject, and (7) there is influence of learning style, family climate, and self confidence on learning outcomes in Mathematics subject by 13% and 87% which are influenced by other factors.